Regenerative and anti‐inflammatory effect of a novel bentonite complex on burn wounds - Ju Young Lee; Han Na Suh; Kwan Young Choi; Chang Woo Song; Jeong Ho Hwang (Veterinary Medicine and Science, 2022)
Abstract Background Bentonite, a montmorillonite clay, has been used as a classical remedy strategy for a long time. Recently, bentonite has been used as a raw material in cosmetic products because of its antibacterial and antioxidant properties. However, the therapeutic effect of bentonite on burn injuries has not yet been identified. Objectives The aim of this study was to explore the therapeutic effect of a novel bentonite complex, which was developed for medical use, on burn wounds and the anti‐inflammatory function of bentonite clay in the complex in vitro. Methods A novel bentonite complex and bentonite clay were prepared for each in vivo and in vitro assay (C&L Biotech, Seoul, Korea). Burn wounds were induced on the dorsal skin of two Yucatan minipigs, and effects of tissue regeneration and anti‐inflammation were assessed by histological and gene expression analysis. Results The bentonite complex improved skin regeneration in burn wounds by inducing collagen synthesis, cell proliferation and angiogenesis in vivo. Furthermore, expression of inflammatory cytokines was significantly inhibited by treatment of the bentonite complex. In vitro study for identification of anti‐inflammatory effect showed that bentonite clay significantly regulated COX‐2 signalling in both HacaT keratinocytes and 3D4/2 macrophage cell lines. Conclusions This study identified the therapeutic effect of a novel bentonite complex in burn wounds by inducing skin regeneration and bentonite‐mediated anti‐inflammatory responses.